2014
DOI: 10.3892/mco.2014.479
|View full text |Cite
|
Sign up to set email alerts
|

Polaprezinc reduces the severity of radiation-induced mucositis in head and neck cancer patients

Abstract: Abstract. Polaprezinc (PZ), an antiulcer drug, has been reported to have antioxidant properties. The aim of the present study was to assess the feasibility and efficacy of administering PZ for radiation-induced mucositis in head and neck cancer patients. Patients with newly diagnosed head and neck cancer were enrolled in this prospective study. PZ was prepared as an oral rinse. The PZ oral rinse was used four times per day during the course of radiotherapy. Sequential changes in radiation mucositis were assess… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 10 publications
0
13
0
Order By: Relevance
“…The efficacy of systemic zinc in preventing OM in H&N cancer patients was also evaluated in 2 case-control studies demonstrating conflicting results [11,12].…”
Section: Zinc (Systemic): Handn Cancer Rt/rt-ct-prevention Guideline: mentioning
confidence: 99%
“…The efficacy of systemic zinc in preventing OM in H&N cancer patients was also evaluated in 2 case-control studies demonstrating conflicting results [11,12].…”
Section: Zinc (Systemic): Handn Cancer Rt/rt-ct-prevention Guideline: mentioning
confidence: 99%
“…Our previous study reported the efficacy of PZ for acute radiation proctitis in a rat model and demonstrated the anti-inflammatory effect of PZ on radiation-induced mucosal damage ( 6 ). In addition, the clinical use of PZ has been reported to be feasible and can increase a patient's QOL during radiotherapy ( 8 , 9 ).…”
Section: Discussionmentioning
confidence: 99%
“…There is, however, little data of the negative effects of PZ use for tumor control and the survival outcomes of the patients who received PZ as a supportive treatment have been poorly understood. However, no direct evidence has suggested that the use of PZ can lead to inferior tumor outcomes in patients with malignancies ( 8 , 9 ). Watanabe et al ( 8 ) reported that the initial responses of tumors to radiotherapy were not affected by the PZ intake in a randomized clinical trial.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Polaprezinc, a zinc complex of L-carnosine, is widely used as a gastric mucosal protector to treat gastric ulcers and a previous study revealed it may inhibit liver fibrosis in mice (20). Although, it was believed that HSCs are involved in polaprezinc-induced reversal of liver fibrosis, more evidence is required to confirm this hypothesis.…”
Section: Introductionmentioning
confidence: 99%